2014
DOI: 10.3945/an.114.006254
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E Inadequacy in Humans: Causes and Consequences

Abstract: It is estimated that >90% of Americans do not consume sufficient dietary vitamin E, as α-tocopherol, to meet estimated average requirements. What are the adverse consequences of inadequate dietary α-tocopherol intakes? This review discusses health aspects where inadequate vitamin E status is detrimental and additional vitamin E has reversed the symptoms. In general, plasma α-tocopherol concentrations <12 μmol/L are associated with increased infection, anemia, stunting of growth, and poor outcomes during pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
189
1
20

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 220 publications
(217 citation statements)
references
References 136 publications
(124 reference statements)
7
189
1
20
Order By: Relevance
“…Although the recommended amount of vitamin E is higher for men than for women, Dutch women consume less vitamin E more often compared to Dutch men [17] . Data by Traber [18] published last year suggest that more than 90% of United States Americans consume insufficient amounts of vitamin E.…”
Section: Vitamin E Intake: Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the recommended amount of vitamin E is higher for men than for women, Dutch women consume less vitamin E more often compared to Dutch men [17] . Data by Traber [18] published last year suggest that more than 90% of United States Americans consume insufficient amounts of vitamin E.…”
Section: Vitamin E Intake: Recommendationsmentioning
confidence: 99%
“…Next to dietary habits, hereditary disorders are known to cause primary and secondary vitamin E deficiencies or inadequate vitamin E bioavailability [19] . Because the official intake recommedations of vitamen E are so seldom met, along with the rare occurance of deficiency symptoms (apart from being caused by disease, addressed later), Traber [18] recently questioned whether the recommended α-TOH intake is set too high and whether a diet low in dietary α-TOH intake has any biological significance. However as of now, circulating α-TOH concentrations below 9 mmol/L for men or below 12 mmol/L for women are considered as deficient and only marginal for healthy adults, respectively [18] .…”
Section: Vitamin E Intake: Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…24,26,27 In this study influence of socioeconomic characteristics with alpha-tocopherol serum levels and maternal vitamin E deficiency were not found (Table 2), a result similar to a cohort on pregnant women in the Peru. 3 Gurgel et al, 8 observed that women who were attended for childbirth in the private health network were more likely to have satisfactory vitamin concentrations (OR= 0.3; CI95%: 0.1-0.8).…”
Section: Tablementioning
confidence: 54%
“…21,24 Studies show that in low income situations there is a change in food choices, characterized by the acquisition of cheaper items and with high energy density. 7,22,23 The first items that are out of the diet are usually the healthier food, which the population cannot reach the recommended quantities, such as grains of high quality protein, vegetables and greenery, extra virgin olive oil and fresh fruit, 6,22,25 some important sources of vitamin E.…”
Section: Tablementioning
confidence: 99%